KUALITAS PENERIMAAN SINYAL TERJAUH STASIUN TVRI PONTIANAK - Nurhafandi . (Faculty of Engineering, Universitas Tanjungpura, 2017)
Relay TVRI station serves as repeater station TVRI consisting sub-system communication satellite used to transmit the signals of images and sound from central station in Jakarta to relay station in the region. Then a transmitter communication sends signals to the homes viewers who being in the coverage areas. Due to improving the need for information TVRI Pontianak as one of the relay station TVRI belonging to the Indonesian government which is located on Ahmad Yani Street in South Pontianak, West Kalimantan. Relay TVRI station is expected to meet the needs of the required information society. The Station TVRI Pontianak unknown the maximum transmit based on quality of images (video) and sound (audio). The transmitter television station TVRI Pontianak put an antenna has reached 100 meters from the ground, operate on 32 UHF channel using 559,21 MHz frequency. The transmitter of TVRI Pontianak has 2,5 KW transmit power, using an antenna dipole with 32 panels above the towers with each direction consisting of 8 panels antenna where the heading due North 0°, West 90°, South 180° and East 270°. With the number of 32 panels can make a broadcast clearly both in terms of images and sound. Evaluation performance the measurement result of audio and video on broadcast station TVRI Pontianak that are based on the calculation of using formulas terrestrial obtained results at a distance 65,01 Km and condition without obstacles and the measurements of the signal audio and video to Northwest 35,72 Km, East 37,72 Km, Northeast 34,77 Km and West 18,57 Km. The revenue of station TVRI Pontianak can changing depend on high, the gain and geography antenna recipients Kata Kunci : TVRI Pontianak, Sinyal, Audio, Video